Impact of Solar Irradiation on Photosynthetic Activity of Chili (Capsicum annuum L.) Leaves - Sanjayanti, Arum; Ahmad, Deni Nasir; Habibah, Putri; Peria, Maria Yosefina; Fadillah, Zahra (Universitas Sembilanbelas November Kolaka, 2024)
The photosynthetic activity of chili (Capsicum annuum L.) leaves greatly influences sunlight radiation, the role of photosynthesis produces food that can help in plant growth and development. If a plant lacks light, it will not produce chlorophyll so it will be pale in color. Abnormalities in the photosynthesis process will also affect the formation of carbohydrate compounds in the leaves. The carbohydrate content of chili leaves plays an important role in the metabolism of chili plants. This research aims to determine the effect of solar radiation on the photosynthetic activity of chili leaves using the Sach test . This research method uses descriptive methods. Sampling was carried out by purposive sampling and giving the chili leaves a closing and opening treatment using aluminum foil under direct sunlight. The data analysis technique used is a qualitative descriptive analysis model, where this model is included in the type of qualitative research which is described descriptively. The results of the research showed that the parts of the leaves that were exposed to sunlight produced more chlorophyll, the leaf color was darker green, and produced starch which was characterized by a blue-black or dark purple reaction when given an iodine solution. Meanwhile, the parts of the leaves that are not exposed to sunlight show less yield, the color of the leaves is paler or yellowish.Keywords: Sollar Irradiation, Capsicum annuum, Chili Leaf, Photosynthesis